The Effect of The Drill Training Method on The Service Capability of Volkas Volleyball Academy U-17 - Veron, Moh. Shabril Umar Subachtiar; Purwoto, Septyaningrum Putri; Hidayatullah, Fajar; Widodo, Haryo Mukti (Universitas PGRI Palembang, 2024)
One of the basic techniques in volleyball is the serve, which marks the start of the game. Players usually perform the serve with an overhead serve technique so that it can also provide an attack. The aim of this study is to test the effect of drill training on improving overhead serve ability. This study uses a quantitative approach with an experimental research design, involving 20 junior volleyball athletes as subjects. The research was conducted over 6 weeks with a training frequency of 3 times per week. The test instrument used was the AAHPER serving accuracy test. The results of this study showed an increase in the average score from the pre-test (22.8) to the post-test (25.5). The paired sample t-test showed a p-value (sig) of -3.3441, which is smaller than the table value (sig) of 2.10092, indicating a significant difference in the effect of drill training on overhead serve ability.